Rising rural body-mass index is the main driver of the global obesity epidemic in adults - Brenner, Hermann; Jonas, Jost B.; Kaaks, Rudolf; Saum, Kai-Uwe; Schöttker, Ben (Nature, 2019)
Contrary to the view that urbanization is a major driver of the global rise in obesity, the global increase in body-mass index is shown to be mostly due to increases in the body-mass indexes of rural populations.
Gesehen am 05.06.2019
Hermann Brenner, Jost B. Jonas, Rudolf Kaaks, Kai-Uwe Saum and Ben Schöttker are members of the NCD Risk Factor Collaboration (NCD-RisC)